2014
DOI: 10.15288/jsad.2014.75.16
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Specific Parenting, Adolescents' Self-Control, and Alcohol Use: A Moderated Mediation Model

Abstract: ABSTRACT. Objective: There is convincing evidence that parental rules about alcohol are important in curbing adolescents' alcohol use. However, little is known about the mechanisms through which the direct link between alcohol-specifi c parenting and alcohol use is obtained. In this study, we investigated the mediating effect of adolescent self-control on the relationship between alcohol-specifi c rules and adolescents' drinking behavior and whether this mediation effect depends on the level of quality of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 71 publications
0
19
0
5
Order By: Relevance
“…Adolescents are more likely to display open communication with their parents about general topics when they have high PCC (Luk, Farhat, Iannotti, & Simons-Morton, 2010). Parents are more likely to have the opportunity to have frequent conversations and set rules effectively when PCC is high (Cleveland, Gibbons, Gerrard, Pomery, & Brody, 2005;Guilamo-Ramos et al, 2008;Harakeh, Scholte, Vermulst, de Vries, & Engels, 2010;Koning, Van den Eijnden, & Vollebergh, 2014;Maggi et al, 2014). In Chaplin and colleagues' (Chaplin et al, 2014) observational study adolescents' physiological responses were measured during conversations with parents; when parents displayed behaviours suggestive of low PCC, such as criticism and sarcasm, adolescents tended to display higher cortisol levels, which were indicative of greater feelings of discomfort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents are more likely to display open communication with their parents about general topics when they have high PCC (Luk, Farhat, Iannotti, & Simons-Morton, 2010). Parents are more likely to have the opportunity to have frequent conversations and set rules effectively when PCC is high (Cleveland, Gibbons, Gerrard, Pomery, & Brody, 2005;Guilamo-Ramos et al, 2008;Harakeh, Scholte, Vermulst, de Vries, & Engels, 2010;Koning, Van den Eijnden, & Vollebergh, 2014;Maggi et al, 2014). In Chaplin and colleagues' (Chaplin et al, 2014) observational study adolescents' physiological responses were measured during conversations with parents; when parents displayed behaviours suggestive of low PCC, such as criticism and sarcasm, adolescents tended to display higher cortisol levels, which were indicative of greater feelings of discomfort.…”
Section: Resultsmentioning
confidence: 99%
“…This model highlights the moderating relationship between parenting behaviours, such as PCC, and communication about substance use. Others have used this model to contextualise their findings, that general and substance use specific parenting practises influence adolescent substance use, suggesting the importance of considering the theoretical foundation of future studies within the context of parenting practises (de Leeuw et al, 2010;Handley & Chassin, 2013;Harakeh et al, 2010;Huver et al, 2006Huver et al, , 2007Koning et al, 2014). Conversations about substance use must be two-sided, involving explanations around the health implications of using substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family management, including having rules about youth drinking, is negatively associated with youth drinking onset, alcohol use (Järvinen & Østergaard, 2009) and binge drinking (Järvinen & Østergaard, 2009;Spijkerman et al, 2008). Furthermore, the use of alcohol-specific rules is related to the postponement of drinking onset among not-yet-drinking adolescents (Van Der Vorst, Engels, Dekovic, Meeus, & Vermulst, 2007;Van der Vorst et al, 2006a) and also to less adolescent drinking (Koning, van den Eijnden, & Vollebergh, 2014a). Also, lenient rules among parents have been found to increase both the risk of drinking onset and the risk of more regular drinking among adolescents (Koning et al, 2010a).…”
Section: Alcohol-specific Rulesmentioning
confidence: 99%
“…One of the goals of the review was to address the knowledge gap regarding psychological and social pathways that connect sport participation to alcohol and drug use among youth. Results from this review reported that sport was related to increased self-control and self-regulation (Bruner et al, 2011 ; Durlak et al, 2010 ; Gould et al, 2006 ; Johnston et al, 2013 ), factors that other research has found to be robust predictors of reduced alcohol and drug use, including heavy alcohol use (Brody & Ge, 2001 ; Koning, Van den, & Vollebergh, 2014 ; Quinn & Fromme, 2010 ). In addition, quantitative studies within the review found that sport was related to increased self-esteem and mastery along with other indicators of well-being such as decreased depression, anxiety, and suicidal ideation (Babiss & Gangwisch, 2009 ; Barber et al, 2001 ; Harrison & Narayan, 2003 ).…”
Section: Discussionmentioning
confidence: 93%